Organic synthesis - Willis, Christine L; Wills, Martin; Oxford University Press (Oxford ; New York : Oxford University Press, 2007)
This series of short texts provides accessible accounts of a range of essential topics in chemistry. Written with the needs of the student in mind, the Oxford Chemistry Primers offer just the right level of detail for undergraduate study, and will be invaluable as a source of material commonly presented in lecture courses yet not adequately covered in existing texts. All the basic principles and facts in a particular area are presented in a clear and straightforward style, to produce concise yet comprehensive accounts of topics covered in both core and specialist courses. This book introduces a logical approach for the design of synthetic routes to reasonably complex organic molecules from simple starting materials. It describes the concept of 'retrosynthesis', which allows suitable simple starting materials to be identified; the importance of bond polarity and functional group interconversions; how to find an effective route to a target molecule containing more than one functional group; and valuable strategies to adopt when designing syntheses. The text also includes a review of methods for the control of chemo-, regio-, and stereoselectivity, and a discussion of protecting groups. Finally four syntheses of the pyrrolidine alkaloids are compared and contrasted using the principles described in the book. Practice examples are provided throughout the book
Introduction to synthesis -- Retrosynthetic analysis: I, the basic concepts; II, latent polarity and FGIs; III, strategy and planning Selectivity: I, chemoselectivity and protecting groups; II, regioselectivity; III, stereoselectivity -- Selected organic syntheses
Includes bibliographical references and index
Keywords: Organic compounds -- Synthesis; Organic compounds -- Synthesis